2022
DOI: 10.1186/s12887-022-03589-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total anti-oxidant capacity is inversely related to the prevalence of depression in adolescent girls

Abstract: Background Oxidative stress is considered to be a contributory factor for depression, and is affected by the dietary intake of pro-and anti-oxidants. Dietary total antioxidant capacity (DTAC) is an index which is applied to estimate the cumulative power of antioxidants in the whole diet. The aim of this study was to determine the relationship between DTAC and prevalence of depression in adolescent girls. Methods A total of 741 Iranian adolescent gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Data also suggest that lifestyle interventions improve depressive symptoms [ 130 ]. For example, diets with high antioxidant capacity were associated with a lower prevalence of depression [ 131 ]. Additionally, some mitochondrial modulators appear to be effective in the management of depression, notably in reestablishing the redox balance [ 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data also suggest that lifestyle interventions improve depressive symptoms [ 130 ]. For example, diets with high antioxidant capacity were associated with a lower prevalence of depression [ 131 ]. Additionally, some mitochondrial modulators appear to be effective in the management of depression, notably in reestablishing the redox balance [ 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship has been shown between the way people eat and the risk of depression, anxiety, and stress disorders [125][126][127]. The total antioxidant capacity of the diet consumed is inversely correlated with depression and some biomarkers of oxidative stress in menopausal, postmenopausal, and diabetic women [128][129][130], as well as in young women and girls [131][132][133]. The study by de Oliveira et al [130] performed in Brazil showed that depressed women consumed fewer polyphenols than healthy women, which may indicate the importance of this group of food ingredients in the prevention of depressive disorders.…”
Section: Foods Containing Polyphenols As Part Of Diet Therapy In Depr...mentioning
confidence: 99%